An introspection of quality of novel drug approvals by United States Food and Drug Administration - Mehani, Rekha; Shukla, Ajay K. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: United States Food and Drug Administration (FDA) is the fastest drug review agency in the world. FDA is responsible for protection of the public health by assuring that foods are safe, wholesome, sanitary and properly labelled. Approved Novel drugs are often innovative products that serve unmet medical needs or otherwise help to advance patient care. Methods: FDA novel drug approvals were analysed from calendar year (CY) 2012 to 2016 on the basis of three criteria i.e., impact, access and predictability. Impact measured on the basis of: percentage of novel drug approvals (a) first in class (b) for rare diseases. Access measured on the basis of: percentage of novel drug approvals (a) first cycle approval (b) approval in the U.S. before other countries and (c) percentage of priority reviews. Predictability measured by: the percentage of novel drug approvals that met the PDUFA goal dates for the application review. Results: Total number of novel drugs approved from CY 2012 to 2016 was 176 (average 35 novel drugs/ year). Impact of novel drug approvals: 40% were first in class and 39% were for rare diseases. Access of novel drug approvals: 84% were first cycle approval, 60% were approval in US before other countries, 51% priority reviews among novel drug approvals. Predictability of novel drug approvals: 97% approvals able to meet PDUFA goal dates for application review. Conclusions: Novel drug approvals during CY 2012-2016 had a high quality which is very much evident by their high impact, good access and high predictability.